Sixth-grade students' engagement in academic tasks. Issue 2 (4th March 2018) - Parsons, Seth A.; Malloy, Jacquelynn A.; Parsons, Allison Ward; Peters-Burton, Erin E.; Burrowbridge, Sarah Cohen
ABSTRACT: Student engagement is important for teachers and researchers because it is associated with student achievement. Guided by self-determination theory, this year-long case study used observations and interviews to examine six students' behavioral, affective, and cognitive engagement in integrated literacy and social studies tasks. Task differences were rated according to the degree to which tasks were authentic, collaborative, challenging, student directed, and sustained. Results demonstrated that, overall, students were more engaged in tasks that include a higher degree of these elements. In particular, students reported that they were engaged in tasks that included collaboration, new learning, and teacher support.